Yuval N. Harari: Freedom Blurred and Demystified: (Part two) - Beorlegui, Carlos (Razón y fe, 2021)
Reading the texts of the writer Yuval Noha Harari produces a series of very conflicting feelings: from admiration to perplexity. Admiration and perplexity due to his great capacity for synthesis, his highly successful neologisms, his contribution of suggestive and accurate ideas, both with respect to the past and to our near future, etc. But Harari also has his limitations, weaknesses, and contradictions. This is especially true when the Israeli intellectual reflects on human freedom, one of his recurring themes, which is present in a special way in his latest works, as well as in his various interviews with the media.